Pengaruh Viral Marketing, Experiential marketing Dan Persepsi Harga Terhadap Minat Beli Ulang produk Mixue Ice Cream & Tea Pada gen Z - Agustinus Herinama, Agustinus; Setiawan, Yuli (Jurnal Manajemen, 2024)
This study aims to determine the effect of viral marketing, experiential marketing, and price perceptions on repurchase interest in mixue ice cream & tea products in Gen Z, both simultaneously and partially. This research design uses quantitative methods with non-probability sampling techniques. The population of this study is Generation Z, which has consumed Mixue at the Gandaria City branch. A sample of 80 respondents used the Roscoe formula. The data analysis method used is multiple linear regression analysis, F test (simultaneous), t-test (partial), and Coefficient of Determination (Adjusted R Square) with the help of SPSS 25 software. This study's results indicate a simultaneous influence between the variables Viral Marketing, Experiential Marketing, and Price Perception on Repurchase Interest. Partially, Viral Marketing and Experiential Marketing have a positive effect on Repurchase Interest. Meanwhile, Price Perception hurts Repurchase Interest. Keywords : viral marketing, experiential marketing, price perception, on repurchase interest.